The Cooperation of the Republic of Kazakhstan on issues regarding the International Security (Journal of actual problems of jurisprudence, 2018)
In the following article, the author analyzes the international situation and raises the questions about the need of strengthening the relationship between the countries in order to fight against the threats of international terrorism. Kazakhstan is a sovereign country that is located in a special geopolitical position and plays an important role in providing the international security. Therefore, one of the most significant directions in providing the international security in Kazakhstan and maintaining the peace in the region is the creation of the appropriate legal foundation, which includes both the internal legal base and international agreement that has a purpose of solving issues regarding the international security. Key words: the international law, the international security, the national security, the public security, the political security, the informational security, the economic security.